Close association of a DNA replication origin and an ARS element on chromosome III of the yeast, Saccharomyces cerevisiae. - Huberman, J A (1988)
Two dimensional gel electrophoretic techniques were used to locate all functional DNA replication origins in a 22.5 kb stretch of yeast chromosome III. Only one origin was detected, and that origin is located within several hundred bp of an ARS element.